Full-length transcriptome analysis revealed that 2,4-dichlorophenoxyacetic acid promoted in vitro bulblet initiation in lily by affecting carbohydrate metabolism and auxin signaling - Gao, Cong; Zhang, Lin; Xu, Yunchen; Liu, Yue; Xiao, Xiao; Cui, Liu; Xia, Yiping; Wu, Yun; Ren, Ziming (Frontiers in Plant Science, 2023)
Bulblet initiation, including adventitious bud initiation and bulblet formation, is a crucial process for lily and other bulbous flowers that are commercially propagated by vegetative means. Here, by a hybrid strategy combining Pacific Biosciences (PacBio) full-length sequencing and Illumina RNA sequencing (RNA-seq), high-quality transcripts of L. brownii (Lb) and its variety, L. brownii var. giganteum (Lbg), during in vitro bulblet initiation were obtained. A total of 53,576 and 65,050 highquality non-redundant full-length transcripts of Lbg and Lb were generated, respectively. Morphological observation showed that Lbg possessed a stronger capacity to generate bulblets in vitro than Lb, and 1 mg L −1 2,4-dichlorophenoxyacetic acid (2,4-D) significantly increased bulblet regeneration rate in two lilies. Screening of differentially expressed transcripts (DETs) between different stages and Mfuzz analysis showed 0 DAT to 1 DAT was the crucial stage with the most complex transcriptional change, with carbohydrate metabolism pathway was significantly enriched. In addition, 6,218 and 8,965 DETs were screened between the 2,4-D-treated group and the control group in Lbg and Lb, respectively. 2,4-D application had evident effects on the expression of genes involved in auxin signaling pathway, such as TIRs, ARFs, Aux/IAAs, GH3s and SAURs. Then, we compared the expression profiles of crucial genes of carbohydrate metabolism between different This is a provisional file, not the final typeset article stages and different treatments. SUSs, SUTs, TPSs, AGPLs, GBSSs and SSs showed significant responses during bulblet initiation. The expression of CWINs, SUTs and SWEETs were significantly upregulated by 2,4-D in two lilies. In addition, 2,4-D increased the expression of starch degradation genes (AMYs and BAMs) and inhibited starch synthesis genes (AGPLs, GBSSs and SSs). SBEs were significantly upregulated in Lbg but not in Lb. Significant co-expression was showed between genes involved in carbohydrate metabolism and auxin signaling, together with transcription factors such as bHLHs, MYBs, ERFs and C3Hs. This study indicates the coordinate regulation of bulblet initiation by carbohydrate metabolism and auxin signaling, serving as a basis for further studies on the molecular mechanism of bulblet initiation in lily and other bulbous flowers.